Efeito neuroprotetor da Spirulina platensis no parkisionismo experimental induzido pela 6-OHDA - Lima, Francisco Arnaldo Viana (2018)
Parkinson's disease (PD) is a neurodegenerative movement disorder affecting 1% of the population in the 65-year age group, characterized by the degeneration of dopaminergic nigrostriatal neurons in the pars compacta substantia. The current treatment of PD is restricted to symptomatic relief, and to date there are no agents capable of reducing neuronal degeneration. Spirulina platensis (Arthrospira) (SPI) is a cyanobacterium that can contain up to 74% of proteins, exhibiting anti-inflammatory and antioxidant actions. Considering the importance of inflammation and oxidative stress in Parkinson's disease (PD), the possible SPI neuroprotective effects were evaluated in a PD model. Male Wistar rats were divided into: False operated (FO), untreated 6-OHDA and 6-OHDA treated with SPI (25 and 50 mg / kg, v.o.). The neurotoxin was injected into the right striatum through stereotactic surgery and the treatments with SPI began 2 h after surgery lasting 18 days. FO and the 6-OHDA group were treated with distilled water only during the same period. After 15 (fifteen) days after surgery, all the animals were submitted to behavioral tests; after the tests were euthanized by decaptation for dissection of the following brain areas: right (injured) striatum and left striatum to perform the neurochemical and biochemical analyzes or perfused for the immunohistochemical assays. SPI (25 and 50 mg / kg) reduced the rotational behavior induced by apomorphine, increased levels of DA and DOPAC and decreased levels of nitrite and TBARS. In addition, the immunoreactivities for iNOS, COX-2 and GSK3β in the untreated injured striatum were significantly reduced after treatment with the SPI compared to the untreated group. Immunoblotting to TH, DAT, SOD-2 was increased following treatment with SPI in the injured striatum, as well as neuronal death was attenuated in the injured striat after treatment with SPI as shown by histopathological staining with Fluoro-jade C. In conclusion, we have shown that behavioral and neurochemical changes in hemiparkinsonian rats were significantly reversed by treatment with SPI, characterizing the neuroprotective potential of Spirulina and stimulating translational studies that focus on the use as an adjunctive treatment for PD.